Pengaruh Motivasi Kerja, Disiplin Kerja, dan Pengembangan Karir terhadap Kinerja Guru: (Studi Kasus pada Guru SMK Kartika X-2 Jakarta) - Deti Putri Ayu Ningsih; Widi Wahyudi (Jurnal Penelitian Ekonomi Manajemen dan Bisnis, 2025)
This study aims to examine the impact of work motivation (X1), work discipline (X2), and career development (X3) on teacher performance (Y) at SMK Kartika X-2 Jakarta. The research employed a quantitative approach with probability sampling, specifically saturated sampling, where all members of the population were included in the sample. A total of 45 respondents participated in the study. Data analysis was conducted using descriptive statistics and multiple linear regression with SPSS V.22. The regression equation derived from the analysis is Y = -6.296 + 0.471 X1 + 0.039 X2 + 1.081 X3 + €. The findings indicate that work motivation has a positive and significant effect on teacher performance, suggesting that teachers who are motivated tend to perform better in their duties. On the other hand, work discipline showed a positive but not significant effect, implying that while discipline is important, it does not directly influence teacher performance in this study. Lastly, career development was found to have a positive and significant effect on teacher performance, highlighting the importance of professional growth opportunities in enhancing teaching effectiveness. These findings suggest that schools should focus on improving teacher motivation and career development programs to boost overall performance, while also addressing work discipline to some extent. Further studies could explore other factors that might influence teacher performance